(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: the aim of this pilot study was to evaluate whether proprioceptive-motor training using the Wii Balance Board (WBB) might improve postural sway in healthy subjects. Methods: twenty-five healthy subjects were trained for six weeks (two sessions per week) with 5 “video games”: Wii Fit Plus (WFP) program. Before and after training: Basic Balance, Single-leg Balance, Agility, Stability and Motion (lower limb: right-left and both leg) were measured using the Wii Balance Board. Results: the Wilcoxon Test showed improvements at the end of the training program compared to the baseline conditions. Basic Balance increased during the WFP (33.33%) and was associated with a 19.92% decrease in center of pressure (COP) lenght. The Single-leg Balance results incremented after the WFP (left 29.09% vs. right 47.92%) and accompanied by a decrement in COP (left 28.71% vs. right 30.45%). The values for the Agility test increased both in WFP and COP (28.57% and 58.57%, respectively). The Stability test scores increased in the WFP (66.67%) along with a consequent decrease in COP (10.53%). Finally, the Motion test values increased in the WFP (73.17%), whilst COP for this test decreased (12.02%). These results indicate that 6 weeks of virtual training produced a good adaptability. Younger participants (<20 years) demonstrated to be more responsive to dynamic stimulation with respect to those >20 years. Conclusions: significant improvements in all participants were observed, indicating that virtual training can influence posture and balance in healthy people. Because of its characteristics of low cost and easy availability, a portable system for balance training for everyone offers the possibility to more readily measure motor skill and to gauge improvement.